Research in social science - Ghosh, Anjan (2004)
A recent workshop brought together research scholars working on eastern India, and by presenting a diverse collection of themes in the papers, went some way towards making up for the gross under-representation of this region in social science research. - Reproduced.
Keywords: Social research